Clinical outcome of total alloplastic temporomandibular joint reconstruction in cases of recurrent ankylosis with emphasis on pitfalls: A retrospective analysis. Issue 1 (January 2019) - Roy Chowdhury, Sanjay Kumar; Saxena, Vivek; Rajkumar, K.; Mishra, Abhishek
Abstract: Aim: The present study is designed to evaluate the pitfalls and complications in treatment of recurrent TM Joint Ankylosis cases using total alloplastic joint replacement. Materials and methods: Data was analyzed retrospectively in terms of maximum mouth opening, deviation during opening of mouth, heterotrophic bone formation, peri-joint infection, and intraoral exposure of joint, post-surgery malocclusion, contralateral TMJ pain. Results: 12 patients (15 joints) of TMJ ankylosis were treated with TMJ replacement in our department. Mean pre-operative maximum inter-incisal mouth opening was 3.92 mm (SD ± 1.73). Post op mean inter-incisal opening three month, six month and one year were 31.59 mm, (SD ± 3.15) 32.25 mm(SD ± 1.82), 32.67 mm (SD ± 2.19)respectively. There were 2 cases of malocclusion, 1 case of infection and 1 case of intra-oral exposure of joint. Conclusion: The success rate available in literature for use of alloplastic joint replacement in treatment of end stage TMJ disorders which includes a large area of different types of temporomandibular joint disorders cannot be implicated. In our study we found complication free success rate of 67%. A large study focusing specifically on use of alloplastic joints in recurrent ankylosis cases is needed for the subcontinent.